Evaluation of the Effectiveness of Unplugged Computational Thinking Training Program for Teachers using ABCD Discrepancy Model - Mei Prabowo; Burhan Yusuf Habibi; Mowafg Masuwd (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
The ABCD discrepancy evaluation technique is used in this study to assess the efficacy of Computational Thinking (CT) Unplugged instruction at the school level. In order to find discrepancies between anticipated and actual training outcomes, the study looked into the four model components: trainers and program implementers, program and its execution, objectives, and impact. We conducted in-depth interviews with trainee teachers to learn more about the procedure, issues, and difficulties encountered while putting CT into practice. Purposive sampling was employed in this study to examine the effects of CT training on trainee teachers' personal experiences and outcomes. The findings demonstrate that while CT can raise teaching's effectiveness and efficiency, its performance in classrooms can be enhanced by instructors' attitudes toward and commitment to training, as well as by the organizers' technical support and deliberate program monitoring. On the basis of these conclusions, suggestions are presented to enhance the way that CT is used in schools. This study helps us comprehend the opportunities and difficulties of integrating CT in classrooms.